FINITE ELEMENT STUDY OF VOID BEHAVIOR UNDER LOW STRESS TRIAXIALITY - LIU MeiMei; CHEN JianJun; PAN HongLiang (Jixie qiangdu)
Based on finite element simulation,a 3D cell model subjected to low stress triaxiality,with a spherical void located in center was developed. The distribution rule of stress and strain was investigated,as well as the developing trend of volume of void and matrix. The analysis indicated that there are some limitations of the theories which regarded void volume fraction as damage parameter. Further research was carried out to verify the reliability of the fracture strain as element failure parameter by analyzing the results of uniaxial tension simulation and experiment. More investigation was conducted to analyze the void growth and material failure under low stress triaxiality by introducing critical equivalent plastic strain as failure criterion.